2011
DOI: 10.1128/jvi.02433-10
|View full text |Cite
|
Sign up to set email alerts
|

Penaeus monodon TATA Box-Binding Protein Interacts with the White Spot Syndrome Virus Transactivator IE1 and Promotes Its Transcriptional Activity

Abstract: We show here that the white spot syndrome virus (WSSV) immediate-early protein IE1 interacts with the Penaeus monodon TATA box-binding protein (PmTBP) and that this protein-protein interaction occurs in the absence of any other viral or cellular proteins or nucleic acids, both in vitro and in vivo. Mapping studies using enhanced green fluorescent protein (EGFP) fusion proteins containing truncations of IE1 and PmTBP delimited the interacting regions to amino acids (aa) 81 to 180 in IE1 and, except for aa 171 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 47 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…After expression of ie1 , WSSV IE1 protein (a viral transcription factor) is then able to facilitate expression of the viral early genes. WSSV IE1 has been shown to accomplish this through cooperation with P. monodon TATA box-binding proteins (PmTBP) in transcription initiation [ 116 ].…”
Section: Wssv Infectionmentioning
confidence: 99%
“…After expression of ie1 , WSSV IE1 protein (a viral transcription factor) is then able to facilitate expression of the viral early genes. WSSV IE1 has been shown to accomplish this through cooperation with P. monodon TATA box-binding proteins (PmTBP) in transcription initiation [ 116 ].…”
Section: Wssv Infectionmentioning
confidence: 99%
“…Based on detailed mapping of IE1 promoters, progress has been made in understanding the cellular regulation of IE1 expression. Several transcription factors have been found to affect IE transcription, including shrimp homologs of STAT (7,8), NF-B (9,10), and a TATA box binding protein (11). JAK-STAT and NF-B pathways are believed to be critical for antiviral defense (12,13); therefore, the findings for WSSV indicate that this virus takes advantage of the host immune system to assist its own proliferation.…”
mentioning
confidence: 99%
“…JAK-STAT and NF-B pathways are believed to be critical for antiviral defense (12,13); therefore, the findings for WSSV indicate that this virus takes advantage of the host immune system to assist its own proliferation. The biological significance of IE1 during WSSV infection was demonstrated by RNA interference experiments which revealed that depletion of IE1 strongly inhibits the replication of WSSV (11). A recent report showed that the shrimp thioredoxin PmTrx can bind to IE1 and restore its DNAbinding activity under oxidizing conditions, indicating a role for IE1 in WSSV pathogenicity (14).…”
mentioning
confidence: 99%
“…The extracted lysate was centrifuged at 12,000 g for 10 min, and the supernatant was dried using a centrifugal evaporator (CVE-2000, EYELA). The pellet was suspended in a volume of deionized water that was equal WSSV copy number quantification WSSV copy number quantification was performed using the commercial real-time PCR kit for viral load quantification (GeneReach Biotechnology Corp.) as described previously (22). Results were presented as meansstandard deviation.…”
Section: Gsh/gssg Ratio Measurementmentioning
confidence: 99%